Determinants of School Diabetes Care Services and Quality Through the Lens of the School Nurse: A Qualitative Analysis. (1st October 2022) - An, Ruopeng; Li, Danyi; Cole, Marjorie; Park, Katherine; Lyon, Aaron R.; White, Neil
Abstract : Schools play a critical role in students' diabetes management and ensure their safety and well-being. We conducted key informant interviews with 11 school nurses in Missouri to assess determinants for diabetes care implementation. Five themes and 29 subthemes were identified concerning school nurses, schools, external stakeholders, government, and the COVID-19 pandemic. A social-ecological model was developed to elucidate each level's barriers, facilitators, and resources, and their interplay. School nurses should lead diabetes management, emergency planning, and health education for students/staff. Multiple gray areas existed regarding school nurses' specific roles/responsibilities. Lacking funding, insurance, and communication with parents/physicians further challenged diabetes care.